A functional start to computing with Python / Ted Herman. - Herman, Ted, 1952- (Boca Raton : CRC Press, Taylor & Francis, 2014)
'Open source and easy to use, Python offers the availability of exciting libraries of software, application programming interfaces, and even connections to web services. This textbook uses Python as a working environment to teach the basics of computing for students with no prior programming experience. Unlike similar texts, it organizes topics based on a functional first approach to teaching programming. The book includes case studies of practical problems as well as homework and interactive tools online, such as flashcards'--
Includes bibliographical references and index.
Keywords: Python (Computer program language)